Evaluation of the oceanographic measurement accuracy of different commercial sensors to be used on fishing gears. (1st January 2016) - Martinelli, M.; Guicciardi, S.; Penna, P.; Belardinelli, A.; Croci, C.; Domenichetti, F.; Santojanni, A.; Sparnocchia, S.
Abstract: The aim of the paper is to assess the accuracy for physical oceanography purposes of some commercial sensors (Star-Oddi and NKE) installed on fishing boats in the Adriatic Sea. When mounted on fishing gears, they can retrieve huge amounts of daily datasets (temperature, depth and salinity), spanning a very large spatial region. The possibility to establish their accuracy would be of extreme importance for physical oceanography studies since it would be almost impossible to obtain the same amount of data by means of cruises onboard Research Vessels. Comparison tests against a calibrated CTD were performed during several surveys. Summarizing, the data collected by Star-Oddi sensors are useful only considering the data portion where a dwell time at a fixed depth permanence is longer than 50 s, while those collected by NKE sensors are much more accurate for both depth and temperature and could be usefully considered for broader oceanographic purposes. The weak point of the NKE sensors is the salinity measurement. The evaluation carried out in the present study underlined the optimal conditions for the usage of the considered sensors and produced a series of offsets that might be used to enhance the accuracy of the recorded datasets. Highlights: Probes installed on fishing gears may produce valuable oceanographic datasets Optimal conditions for use of non-traditional oceanographic sensors should be defined Comparison experiments may help in definition of offsets for non-traditional probes Datasets with accurate definitions are helpful for operational oceanography purposes